“State of the art” of the rating of perceived exertion scale - Marques Junior, Nelson Kautzner (2013)
In 1860, Gustav Fenchner founded the psychophysical that determines the subjective sensation and perception of stimulus in person. Based in psychophysical, but with the objective of use a rating of perceived exertion (RPE) scale during the exercise, Borg elaborated in the 60`s a scale for monitoring the intensity of the physical exertion. The review article has the objective of presents the “state of the art” of the RPE scale. In this review literature were to selected research on the RPE scale that investigated this instrument during the exercise. The collection of the studies occurred in Bireme, PubMed, Google Scholar and in the CAPES Journals. The results of the review detected that in the 60 to 90 years, most studies was on the RPE during the exercise and about the linearity of the Borg scale in relation some physiological measure. In 1990, the Borg scale was used to prescribe a session. In the 2000 years, most research was on the RPE during the exercise and about the linearity of the Borg scale in relation some physiological measure and some investigation in quantifying of the load through RPE and a study prescribed the training by the Borg scale.